Neuropathic-like pain in fibrous dysplasia/McCune-Albright syndrome - Spencer, TL; Watts, L; Soni, A; Pinedo-Villanueva, R; Heegaard, A-M; Boyce, AM; Javaid, MK (Oxford University Press, 2022)
Context: Pain is a major symptom in adults with fibrous dysplasia/McCune-Albright syndrome (FD/MAS) and response to current treatments, including bisphosphonates and standard analgesics (nonsteroidal anti-inflammatory drugs and opiates) is unpredictable. No studies have explored whether the type of pain is variable in this patient group.